2013
DOI: 10.1152/ajpendo.00269.2013
|View full text |Cite
|
Sign up to set email alerts
|

Whole body metabolic effects of prolonged endurance training in combination with erythropoietin treatment in humans: a randomized placebo controlled trial

Abstract: 1) insulin sensitivity is not improved after ESA treatment despite improved exercise capacity, 2) the calorigenic effects of ESA may be related to increased UCP2 gene expression in skeletal muscle, and 3) training and ESA exert opposite effects on lipolysis under basal conditions, increased FFA levels and liver fat fraction was observed after ESA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 58 publications
12
58
1
Order By: Relevance
“…Previous studies have reported that there may be an association between EPO levels and hypoglycemia, which suggests a potential protective effect of EPO in the treatment of diabetes (1)(2)(3)19,20). The present study demonstrated that treatment with EPO (300 U/kg, three times a week for 4 weeks) was effective in reducing FBG and improving insulin resistance in high-fat diet/low dose STZ-induced experimental diabetic rats.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have reported that there may be an association between EPO levels and hypoglycemia, which suggests a potential protective effect of EPO in the treatment of diabetes (1)(2)(3)19,20). The present study demonstrated that treatment with EPO (300 U/kg, three times a week for 4 weeks) was effective in reducing FBG and improving insulin resistance in high-fat diet/low dose STZ-induced experimental diabetic rats.…”
Section: Discussionsupporting
confidence: 70%
“…Endurance training induces physiological changes that can improve exercise performance in terms of haematopoietic induction, which increases O 2 transport to muscles. This type of training and EPO both stimulate a shift in skeletal muscle, from a fast glycolytic to a slower oxidative phenotype, by inducing mitochondrial biogenesis, which also improves aerobic exercise capacity (28,31,32). Haemoglobin concentration rises because of increased erythrocytes mass, and decreased plasma volume during exercise (10).…”
Section: Physical Activity and Blood Dopingmentioning
confidence: 99%
“…Therefore, in 1990 the International Olympic Committee prohibited rHuEPO use in athletes (26,35 (33). Apart from EPO, other agents are also misused to stimulate erythropoiesis, such as HIFs, even though they induce expression of more than 200 genes, beside EPO gene, or cobalt, although it has serious toxic effects, or prolyl hydroxylase inhibitors, HCP inhibitors, EPO mimetic peptides and recombinant fusion proteins of EPO (26,31,33). Several hormones may also stimulate EPO production, like thyroid hormone, growth hormone, testosterone, angiotensin II, prostanoids (29,33).…”
Section: Physical Activity and Blood Dopingmentioning
confidence: 99%
“…This study examined VLDL-TG and FFA (palmitate) kinetics and oxidation rates of the participants in the C and Tr subgroups with no injections of erythropoiesisstimulating agent. Inclusion criteria (29) required that all participants were untrained, with a VO 2 max !50 ml/kg per min. Additionally, all were normotensive, nonsmokers, used no medication, and had a normal blood count, lipid profile, fasting plasma glucose, HbA1c, and a normal electrocardiogram.…”
Section: Subjectsmentioning
confidence: 99%
“…A detailed description of the study design has been reported elsewhere (29). In brief, in a randomized, paired design, subjects were allocated to a C group (nZ9) or a Tr group (nZ10).…”
Section: Experimental Designmentioning
confidence: 99%